Gene expression analysis of canonical Wnt pathway transcriptional regulators during early morphogenesis of the facial region in the mouse embryo - Murphy, Paula (University of Edinburgh (datashare), 2009)
Structures and features of the face, throat and neck are formed from a series of branchial arches that grow out along the ventrolateral aspect of the embryonic head. Multiple signaling pathways have been implicated in patterning interactions that lead to species specific growth and differentiation within the branchial region that sculpt these features. A direct role for Wnt signaling in particular has been shown. The spatial and temporal distribution of Wnt pathway components contributes to the operation of the signaling system. We present the precise distribution of gene expression of canonical Wnt pathway transcriptional regulators, Tcf1, Lef1, Tcf3, Tcf4 and ?-catenin between embryonic day (E) 9.5 and 11.5. In situ hybridization combined with Optical Projection Tomography was used to record and compare distribution of transcripts in 3D within the developing branchial arches. This shows widespread yet very specific expression of the gene set indicating that all genes contribute to proper patterning of the region. Tcf1 and Lef1 are more prominent in rostral arches, particularly at later ages, and Tcf3 and Tcf4 are in general expressed more deeply (medial/endodermal aspect) in the arches than Tcf1 and Lef1. Comparison with Wnt canonical pathway readout patterns shows that the relationship between the expression of individual transcription factors and activation of the pathway is not simple, indicating complexity and flexibility in the signaling system.
Roles of Skeletal Muscle in Organ Development
PUBLISHED
Keywords: Zoology; Cancer; Genes & Society